ANALISIS BENTUK, FUNGSI DAN MAKNA TUTURAN DALAM TRADISI HOPONG NGAE MASYARAKAT DUSUN UINAO TIMUR DESA HUILELOT KECAMATAN SEMAU - Angel Selvina Adu; Labu Djuli; Narantoputrayadi Makan Malay (Jurnal Lazuardi, 2026)
This research focuses on the forms, functions, and meanings of utterances in the Hopong Ngae tradition of the community of Uinao Timur Hamlet, Huilelot Village, Semau District. The purpose of this study is to describe the forms, functions, and meanings of utterances found in the Hopong Ngae tradition. This research uses a qualitative descriptive method with data collection techniques including observation, interviews, recording, note-taking and documentation. The study refers to the theory of cultural linguistics as well as the SPEAKING components proposed by Dell Hymes as the basis for analysis.The results of the study show that the utterances in the Hopong Ngae tradition consist of three forms, namely the opening form, the main content (core) form and the closing form. These utterances have four functions: informational function, expressive function, persuasive function and interactional function. In addition, the utterances in the Hopong Ngae tradition also contain lexical meaning, grammatical meaning, contextual meaning and symbolic meaning that reflect the values of gratitude, togetherness and respect for God and others in the life of the community.